Currículo cultural das histórias em quadrinhos: Emília e a Turma do Sítio na cartilha da nutrição do Fome Zero - Alcântara, Cláudia Sales de (2008)
Currently the stories in comics are much more accepted as artistic and cultural production by increasingly larger portions of society, being treated as an educational tool, teaching very effective, possessing the ability, through its cultural curriculum of fun, a way forward for be, feel, live and to behave in the world. This study examines the comic magazines distributed free to schools by the Federal Government and state and municipal entitled: Emília e a Turma do Sítio na cartilha da nutrição no Fome Zero. A project of the Zero Hunger Program, in which the MDS - Ministry of Social Development and Fight against Hunger - has a contract with the Editora Globo, and had the technical support of FNDE (National Fund for Development of Education) and the Ministries of Health and Education to produce an educational material with the characters of the Turma do Sítio do Picapau Amarelo, addressing the importance of healthy eating habits and based on regional products, coupled with regular practice of physical activity as essential conditions for the promotion of food security and nutrition.